Development of predictive model for stoop and squat postures on physiological and psychophysical responses in manual lifting tasks - Kamarudin, Nor Hafeezah (2019)
Malaysia’s economic growth is led by several industrial sectors and it involves thousands of workers. Even with the increased use of automation and new technology, manual material handling (MMH) still exist in the industry due to high flexibility and low in cost. MMH contributed as major cause of work-related musculoskeletal disorders (MSD) cases in Malaysia as high as 40%. Posture and weight load identified as the leading ergonomic risk factors to MSD during the MMH task. Posture and weight load identified as the leading ergonomic risk factors to MSD during the MMH task. Frequently used postures, stoop and squat were studied since most researchers come to argument about the correct technique as squat were presumed the safest way to lift but stoop were preferred by most workers. The main objective of this study is to develop a predictive model of MAWL for stoop and squat postures in MMH task. The effects of load, frequency and height on both postures were identified together with the effect of physiological and psychophysical responses on male and female subjects. The methodology applied uses a total of 36 healthy male and female subjects between the ages of 20 to 35 years. The experimental lifting task was designed based on different load weights, heights and frequency (independent variables). The effects of the independent variables on physiological (heart rate and energy expenditure) and psychophysical (rating of perceived exertion (RPE) and maximum acceptable weight limit (MAWL)) responses were studied. The predictive models were developed based on the independent and dependent variables analysis. The results showed that the load, frequency and height were significant factors with physiological and psychophysical response of stoop and squat postures. Heart rate, energy expenditure and RPE increases as the load, frequency and height increase. Meanwhile, MAWL decreases as the frequency and height of lifting increases in both postures. Stoop denote higher MAWL than squat posture as it produces lower heart rate and energy expenditure compared to squat. The significant factors (p<0.05) associated with the MAWL predictive models are subjects, height, heart rate and energy expenditure. The model significantly linear towards the stoop (R = 0.957) and squat (R = 0.922). MAWL predictive model successfully demonstrates and provides guidelines in evaluating the safe loads and without exceeding the limits of the workers in stoop and squat lifting postures during MMH task.